Surface Design: proposition of teaching method based on Brazilian cultural values (ModaPalavra e-periódico, 2018)
This paper is related to the proposition of a new methodological approach to design education, dedicated to the creation of surface design projects, with the transposition of elements and values presents in the identity of a brazilian territory. The presentation of results shows the possibility of expanding methodological tools for the development of surface design projects, resulting in a better appreciation of identitary aspects of a particular culture. Becomes valid, thus, the proposition of union between manual and digital techniques applied in the creative process, based on solid research immersion and gathering information about a given cultural object of study. This process increases the capacity for student learning while also increasing the perception of combined cultural values to a territory.
Keywords: teaching design; method; surface design